Analisis Strategi Harga, Strategi Produk, dan Keuntungan Pada Industri Kerupuk Kemplang di Kota Palembang - Hamira Hamira; Bernadette Robiani; Mukhlis Mukhlis (Department of Development Economics, Universitas Sriwijaya, 2019)
This research is aimed to analyze the pricing and product strategy and also profit of fish cracker industry in Palembang. The data used in this research is primary data which is obtained by using interview techniques to 45 fish crackers producers. The data is analyzed by using descriptive qualitative techniques. The results showed that the producers of fish crackers using Mark up pricing method to set up their price. On the average, the mark-up is 41 percent of average cost. The average profit that are received by producers is Rp1.100.288 in a week. It is also found that 77.78 percent producers differentiated their products in shape and taste.